2020
DOI: 10.1101/2020.04.14.040717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A widely distributed hydrogenase oxidises atmospheric H2during bacterial growth

Abstract: 18 19 Diverse aerobic bacteria persist by consuming atmospheric hydrogen (H2) using group 20 1h [NiFe]-hydrogenases. However, other hydrogenase classes are also distributed in 21 aerobes, including the group 2a [NiFe]-hydrogenase. Based on studies focused on 22 Cyanobacteria, the reported physiological role of the group 2a [NiFe]-hydrogenase is to 23 recycle H2 produced by nitrogenase. However, given this hydrogenase is also present in 24 various heterotrophs and lithoautotrophs lacking nitrogenases, it may pl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 65 publications
(114 reference statements)
7
20
0
Order By: Relevance
“…S4) and RuBisCO ( (1), in line with recent inferences of a diverse and abundant H2 sink in soils [3,17,78]. However, a range of taxa also encoded hydrogenases implicated in hydrogenotrophic growth, such as the group 1d and 2a [NiFe]-hydrogenases [37,82], as well as the functionally enigmatic group 1c and 1f [NiFe]-hydrogenases [3,45] ( Fig. S4).…”
Section: And 3)supporting
confidence: 82%
See 1 more Smart Citation
“…S4) and RuBisCO ( (1), in line with recent inferences of a diverse and abundant H2 sink in soils [3,17,78]. However, a range of taxa also encoded hydrogenases implicated in hydrogenotrophic growth, such as the group 1d and 2a [NiFe]-hydrogenases [37,82], as well as the functionally enigmatic group 1c and 1f [NiFe]-hydrogenases [3,45] ( Fig. S4).…”
Section: And 3)supporting
confidence: 82%
“…Classical studies have shown numerous Proteobacteria, for example Ralstonia eutropha and Bradyrhizobium japonicum, grow efficiently on high levels of H2 using the low-affinity group 1d [NiFe]-hydrogenases [27][28][29][30][31][32][33][34]. More recently, diverse taxa have been shown to use group 2a [NiFe]-hydrogenases to grow on H2 at a wide range of concentrations [35][36][37][38][39]. Some bacteria use H2 for multiple purposes; for example, some Mycobacterium species switch between synthesising the growthsupporting 2a hydrogenase and persistence-supporting 1h hydrogenase in response to organic carbon availability [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we also revealed the presence of high numbers of hhyL genes (4.18 × 10 6 –3.39 × 10 7 copies/g soil) in cold desert soils from across the three poles, many of which contained extremely low levels of carbon and nitrogen. We note here that although the qPCR primer are widely implemented ( Constant et al, 2010 , 2011 ; Meredith et al, 2014 ; Khdhiri et al, 2015 ; Piché-Choquette et al, 2016 ), the discovery of high-affinity hydrogenases beyond group 1 h (D. Cowan, personal communication; Greening et al, 2014 ; Islam et al, 2020 ) suggests that the high-affinity hydrogenase gene abundances quantified here are underestimations.…”
Section: Discussionmentioning
confidence: 80%
“…The level of contamination was proportional to the volume of the vial and the mass of rubber (a proxy for the specific surface area in contact with the enclosed gas phase); therefore, form factor and volume of vials have to be considered. For example, serum vials with an increased volume of >100 mL and thus lower exposed surface area relative to volume may still be suitable for gas storage or incubation experiments lasting a few weeks, if treated stoppers are used (Islam et al, 2019(Islam et al, , 2020Kessler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%